1999
DOI: 10.1086/515103
|View full text |Cite
|
Sign up to set email alerts
|

Early Infection in Bone Marrow Transplantation: Quantitative Study of Clinical Factors That Affect Risk

Abstract: Infections remain common life-threatening complications of bone marrow transplantation. To examine clinical factors that affect infection risk, we retrospectively studied patients who received bone marrow transplants (53 autologous and 51 allogeneic). Over a median of 27 hospital days, 44 patients developed documented infections. Both autologous transplantation and hematopoietic growth factor use were associated with less prolonged neutropenia and decreased occurrence of infection (P < or = .05). In a survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 40 publications
3
57
1
3
Order By: Relevance
“…1,2,16,17 In our study we found a significant difference in duration of neutropenia between MR and MU/MM allo-SCT recipients, which was reflected in a tendency to more infectious complications in the latter group. As additional risk factors, MU/MM allo-SCT recipients were more often in second remission and had had more preceding courses of cytoreductive therapy.…”
Section: Bone Marrow Transplantationsupporting
confidence: 47%
“…1,2,16,17 In our study we found a significant difference in duration of neutropenia between MR and MU/MM allo-SCT recipients, which was reflected in a tendency to more infectious complications in the latter group. As additional risk factors, MU/MM allo-SCT recipients were more often in second remission and had had more preceding courses of cytoreductive therapy.…”
Section: Bone Marrow Transplantationsupporting
confidence: 47%
“…We and others have shown that antimicrobial prophylaxis is associated with reduced mortality after HSCT. 3 However, other strategies of preventing BSI after HSCT, such as reducing BSI from gut-derived pathogens like GNR or vancomycin-resistant Enterococcus, deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It has been observed to occur in 13-60% of HSCT recipients. 1,[3][4][5][6][7][8][9][10] The differences in findings of these studies is likely due to factors such as different study designs, study populations, conditioning regimens and prophylactic antibiotic protocols. However, essentially all of the studies cited demonstrated that Gram-positive organisms, particularly coagulase-negative staphylococci and viridans group streptococci, were responsible for most BSI after HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This reduced extrahematologic toxicity may lead to a reduction in infectious complications post transplant, since disruption of the gastrointestinal mucosa and/or damage to other key organs is a significant triggering mechanism of many of the infections that occur post transplant. 8,9 On the other hand, graft-versus-host disease (GVHD) and its treatment has a profound negative impact on immune reconstitution following HSCT, 10 and the impact of RIC regimens on the risk of acute and chronic GVHD is currently uncertain. The potential benefit on the risk of early infections derived from reduction of the intensity of the conditioning regimen may be negated by the immunodeficiency resulting from GVHD and its therapies.…”
Section: Discussionmentioning
confidence: 99%